(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the transformative impact of technology on contemporary teaching methodologies. It delves into how digital tools, online platforms, and emerging technologies like Artificial Intelligence (AI) and Augmented Reality (AR) are reshaping the educational landscape. The discussion encompasses the benefits of personalized learning, increased student engagement, and the challenges educators face in integrating these technologies effectively. By analyzing current trends and case studies, the article aims to provide insights into the future of education in a technologically advanced society.